Crashworthiness Evaluation of a Parallel 5-Tube Circular Multi-Segment Crash Box with Cutting Die Trigger for Railway Safety - Muhammad Vendy Hermawan; Moch. Agus Choiron; Anindito Purnowidodo; Winarto Winarto (Automotive Experiences, 2025)
This study presents a crashworthiness evaluation of a Parallel 5-Tube Circular Multi-Segment Crash Box with a cutting die trigger, designed to promote controlled progressive folding for high-speed railway applications. The crash box integrates four primary tubes and one secondary tube in a parallel configuration, featuring multi-segment wall thickness and a die-trigger mechanism designed to initiate controlled folding from the tube’s end. The die acts as a deformation initiator, guiding the folding sequence to occur progressively, thereby improving energy dissipation and reducing peak impact forces. Two impact models, namely the Cutting Die Model (CDM) and the Flat Model (FM), were employed to investigate the combined effects of trigger mechanism, multi-segment wall thickness, and impact direction using validated finite element simulations supported by quasi-static and drop-test experiments. Finite Element Analysis (FEA) simulations using ANSYS LS-DYNA were conducted to assess key crashworthiness indicators, including maximum crushing force (Fmax), energy absorption (EA), specific energy absorption (SEA), mean crushing force (Fmean), and crushing force efficiency (CFE). Experimental validation through quasi-static and drop tests confirmed the reliability of the simulation results. The findings reveal that the CDM configuration significantly outperforms the FM model, exhibiting lower Fmax and higher EA, SEA, and CFE values. Progressive folding initiated by the die mechanism enables more stable and efficient energy dissipation. Additionally, the impact direction influences deformation behavior, with the tâ‚”“tâ‚‚ configuration yielding superior performance. These results demonstrate the effectiveness of the proposed crash box design in meeting the stringent safety and spatial requirements of modern railway systems.